The task dependent differences in electromyography activity of hamstring muscles during leg curls and hip extensions - Hirose, N.; Kagaya, Y.; Tsuruike, M. (PLOS ONE, 2021)
This study aimed to investigate the influence of the task type on the relative electromyography (EMG) activity of biceps femoris long head (BFlh) to semitendinosus (ST) muscles, and of proximal to distal regions during isometric leg-curl (LC) and hip-extension (HE). Twenty male volunteers performed isometric LC with the knee flexed to 30° (LC30) and 90° (LC90), as well as isometric HE with the knee extended (HE0) and flexed to 90° (HE90), at 40% and 100% maximal voluntary contraction (MVIC). Hip position was neutral in all conditions. EMG activity was recorded from the proximal and distal region of the BFlh and ST muscles. BFlh/ST was calculated from the raw root-mean-square (RMS) amplitudes. The RMS of 40% MVIC was normalized using MVIC data and the proximal/distal (P/D) ratio of normalized EMG (NEMG) was calculated. The BFlh/ST ratio was higher in HE0 than in LC90 during MVIC and 40% MVIC (p<0.05), and was higher in HE90 than in LC90 (p<0.05) during 40% MVIC at the proximal region, whereas no difference was observed between HE0 and LC30. There was no inter-task difference in BFlh/ST ratio in the distal region. Furthermore, the P/D ratio was higher in LC90 than in LC30 and HE0 (p<0.05) in BFlh and ST muscles, and was higher in HE90 than in LC30 and HE0 (p<0.05) in BFlh during 40% MVIC. However, there was no difference in P/D ratio between LC30 and LC90, and HE0 and HE90. This showed that there was no task-dependent difference iHirose N, Kagaya Y, Tsuruike M (2021) The task dependent differences in electromyography activity of hamstring muscles during leg curls and hip extensions. PLoS ONE 16(2): e0245838. https://doi.org/10.1371/journal.pone.0245838n the EMG activity of the BFlh muscle relative to the ST muscle between prone hip extension and prone knee flexion when the knee joint was set at an equivalent angle. Similarly, there was no task-dependent difference in the NEMG of the proximal region relative to the distal region in BFlh and ST muscles during 40% MVIC.